Value Changes of Lebak Swamp Land over Time in Jakabaring South Sumatra - Elisa Wildayana; Apriadi S Busri; M. Edi Armanto (Center for Journal Management and Publication, 2016)
The research aimed to assess value changes of lebak swamp land over time in Jakabaring South Sumatra. This study was conducted in Jakabaring located in the Southern part of Palembang city. The research used mix methods of quantitative and qualitative approaches and describe the research area. The research resulted that Jakabaring area can be divided into three regions, namely North Jakabaring (around 1,544.13 ha or 57.19 %), East Jakabaring (about 809.46 ha or 29.98 %) and South Jakabaring (around 346.41 ha or 12.83 %). Total population was around 232.369 people in 2000, becoming 262.390 in 2015 and 280.692 people in 2030. High population increase will pressure to land use changes. Population increase and land use changes cannot be avoided, but they can be only managed properly. The order of land use dominance before landfills was namely lebak swamp, settlement/industry, rice fields, swamp bush, agriculture fields, swamp forest, infrastructure, fish ponds, and garden including open spaces. In 2030 it will predictably change, i.e. settlement/industry, garden including open spaces, swamp bush, infrastructure, fish ponds, lebak swamp, rice fields, agriculture fields, and swamp forest. Almost all types of land use changes are driven by the government, meaning that the government is very dominant in determining land use change, whereas the private sector plays only a small role in the land use changes especially for lands with high economic impacts. Land use change initiated by the farmers is very limited and the smallest because farmers are just to seek a livelihood at small-scale level.